Cheilanthes tomentosa Link (Pteridaceae) new addition to the recorded Pteridaceae species in Iraq. Issue 1 (June 2021) - Maulood, B.K.; Ismail, A.M.; AL-Amery, M.M.; AL-Khasreji, T.O.
Abstract: During a survey of Iraqi flora 2010 onward, which is undertaken by Howler Botanical Garden, an interesting fern is recorded. The taxon is identified as Cheilanthes tomentosa Link., based on morphology and anatomy characters. To the best of our knowledge, C. tomentosa has not previously been reported in Iraq. Therefore, the species represent a new addition to the Iraqi flora.